Effect of Lower Limb Strengthening Exercises on Severity of Restless Leg Syndrome among Diabetic Patients: A Time Series Study: Restless Leg Syndrome among Diabetic Patients - Sadaqat, Amina; Ahmar, Kainat; Javed, Hafiza Rabia; Hamid, Ayesha; Shahid, Hira (Pakistan Journal of Health Sciences, 2023)
A disorder characterized by aching or burning sensations in the lower and rarely the upper extremities that occur prior to sleep or may awaken the patient from sleep. Objective: To evaluate the effect of lower limb strengthening exercises on the severity of restless leg syndrome (RLS) symptoms among diabetic patients. Methods: The time series Quasi experimental study design was conducted in the government sector (Services hospital) of Lahore for a sample size of 77 diabetic patients who were also suffering from RLS. In order to compensate dropout’s data were collected from 150 patients, from March 2018 to September 2019. IRRLSG Criterion was used to screen out presence of RLS in diabetic patients. After taking written informed consent, baseline data were collected through a questionnaire of close ended questions and proformas with pictures of lower limb muscle strengthening exercises was given to all patients. Follow-ups were taken twice through phone calls after every four weeks and the difference in the scores was noted down in both groups. Results: Patients who performed strengthening exercises reported reduced symptoms of RLS whereas those who didn’t perform exercises were excluded from the study. 96% patients reported reduced symptoms. While 4 patients did not have any improvement in their symptoms. At the end of 8 weeks majority had a significant improvement in the severity of their symptoms. Conclusions: It is concluded that an exercise program consisting of different strengthening exercises was effective in improving symptoms of RLS. No effort was made to discontinue medications that may aggravate RLS symptoms.